Analysis and characterization of phosphinic pseudopeptides by capillary zone electrophoresis - Koval, Dusan; Kasicka, Václav; Jirácek, Jirí; Collinsová, Michaela; Garrow, Timothy A (Electrophoresis, 2002)
Capillary zone electrophoresis (CZE) was applied to analysis and characterization of phosphinic pseudopeptides with the general structure N-Ac-Val-Ala(psi)(PO2(-)-CH(2)) Leu-Xaa-NH(2), where Xaa represents one of 20 proteinogenic amino acid residues. Pseudopeptides containing neutral or acidic amino acid residues in position Xaa were analyzed as anions in weakly alkaline (pH 8.1) Tris-Tricine background electrolyte (BGE), pseudopeptides with basic amino acid residues in position Xaa were analyzed as cations in acid BGEs (Tris-phosphate buffers). Acidity of phosphinic acid moiety in peptides with basic amino acid residues was determined from the dependence of effective mobility of these peptides on pH in the acid pH region (pH 1.4-2.8). Additionally, separation of diastereomers of some peptides was achieved.
Keywords: osmolární koncentrace; Peptides; peptidy; kyseliny fosfinové; Electrophoresis, Capillary; elektroforéza kapilární; Osmolar Concentration; Phosphinic Acids